2015
DOI: 10.1039/c4sc02907k
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the nature of Cu sites in the activated Cu-SSZ-13 catalyst for SCR reaction

Abstract: X-ray absorption and emission spectroscopy, FTIR and DFT unravel the major Cu species in the activated Cu-SSZ-13 catalyst for NH3-SCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
512
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(567 citation statements)
references
References 71 publications
(153 reference statements)
54
512
0
1
Order By: Relevance
“…These two locations for the Cu ions are well known from structural analysis of Cu-CHA catalysts, although some controversy exists on which form actually constitutes the active site. 6,12,28,34,[39][40][41]44,52,72,73 However, when adsorbates are present, the Cu ion is lifted out of the 6-ring plane and the preference for the 6-ring location diminishes. 42,43,74 This is also observed for the formation of Cu 2+ −NO 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 (step 1), where the difference in energy for the Cu located in the 8-ring is only 0.08 eV lower compared to the Cu in the 6-ring, showing that there is no real preference for location of the Cu in the 6-ring or 8-ring in this case.…”
Section: Verification Of the Reaction Schemementioning
confidence: 99%
“…These two locations for the Cu ions are well known from structural analysis of Cu-CHA catalysts, although some controversy exists on which form actually constitutes the active site. 6,12,28,34,[39][40][41]44,52,72,73 However, when adsorbates are present, the Cu ion is lifted out of the 6-ring plane and the preference for the 6-ring location diminishes. 42,43,74 This is also observed for the formation of Cu 2+ −NO 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 (step 1), where the difference in energy for the Cu located in the 8-ring is only 0.08 eV lower compared to the Cu in the 6-ring, showing that there is no real preference for location of the Cu in the 6-ring or 8-ring in this case.…”
Section: Verification Of the Reaction Schemementioning
confidence: 99%
“…report that the loss of water during dehydration of Cu-CHA typically reaches a plateau at 220-250 °C. [1,39] This temperature is sufficiently low that disturbance of covalent framework bonds and mobility of copper and alumina species is negligible. Upon dehydration, the spin Hamiltonian parameters of all the copper species in the zeolites change substantially and the EPR intensity decreases.…”
Section: Dehydrated Cu-zeolitesmentioning
confidence: 99%
“…if all Cu(II) were reduced). A possible explanation for this could be that it has previously been shown that Cu-SSZ-13-a has two different Cu sites occupied in the crystal structure at 250 °C one in the six ring and one in the centre of the eight rings present in chabazite and it may be possible for the NH 3 activated Cu reduction to be occurring at only one of these sites [18].…”
Section: Further Operando Xas Experiments On Cu-ssz-13-amentioning
confidence: 99%
“…There are two highly preferable sites within the framework, in 8r window connecting cha cages and in the corners of the d6r cages, [17][18][19]. At low temperatures, the 8r site is preferable, enabling the formation of large Cu 2+ species such as [Cu(NH 3 )] 2+ when in the presence of NH 3 [20], however, upon a modest temperature increase (250 °C) the d6r window becomes favourable [21].…”
Section: Introductionmentioning
confidence: 99%